Framing National Leadership: A Discourse Analysis of Prabowo Subianto’s Inaugural Speech Using James Paul Gee’s Seven Building Tasks of Language - Wiguna, Riefki Fajar Ganda (LPPM Universitas Pekalongan, 2025)
This paper analyzes the 2024 inaugural speech of Indonesian President Prabowo Subianto through the lens of James Paul Gee's Seven Building Tasks of Language, a framework that enables a critical exploration of how language constructs and enacts social realities. The study investigates how Prabowo’s discourse performs various linguistic functions that shape political meaning, reinforce collective identities, and articulate ideological positions. By applying Critical Discourse Analysis (CDA) as a methodological foundation, this research reveals the ways in which language is used to assign significance to national challenges, promote specific social practices, construct relational identities between the speaker and the audience, and negotiate the distribution of social goods such as welfare, justice, and public trust. Furthermore, the speech connects Indonesia’s historical struggles with its contemporary aspirations, while mobilizing religious, cultural, and technological sign systems to legitimize the speaker’s vision and authority. Through Gee’s framework, the speech emerges as a rich site of political meaning-making, wherein nationalism, moral accountability, and calls for unity are not merely expressed, but actively constructed through strategic linguistic choices. Ultimately, the analysis shows how political language serves as a powerful tool for leadership legitimacy, public persuasion, and the performative shaping of national identity.